The Development of a Mobile Application Using Scrum Pattern for Monitoring Project Information System - Bulan Ayu Sari Muntai; Eko Darwiyanto; Rio Nurtantyana (Indonesian Journal on Computing (Indo-JC), 2024)
Project monitoring is an important aspect of project management that can affect project success. In interviews with PT Gerbang Sinergi Prima (GSP) stakeholders, project monitoring is still uses manual ways to make the process more efficient and accurate. As a result, it causes delays, cost overruns, or even project failure. Hence, this research aims to develop a mobile application for project monitoring at GSP. The development of the GSP project monitoring mobile application uses a Scrum pattern based on Agile methodology and testing with black-box and user accepted testing (UAT). The Scrum pattern could help the development team produce effective and efficient mobile application development according to changing project needs. The results showed that project monitoring using mobile applications has a positive effect on the effectiveness of project monitoring. Black box testing results showed 100% success on nine modules, ensuring all features functioned adequately. UAT showed 74% positive statements that met user needs and 46% negative statements indicating the application was quite convenient. Furthermore, the mobile project monitoring application is consistently and continuously used for all ongoing projects in the company. We suggested that it is necessary to conduct training for new users of the mobile project monitoring application.